Strategies for Translating Climate Change Texts of Natural Resources Defense Council (Nrdc) Website for Global Audiences - Rafa Hanishaffira; Benny Krisbiantoro (Program Studi Diploma Tiga Bahasa Inggris Fakultas Ilmu Budaya Unsoed, 2023)
This study is entitled “Translating Climate Change Texts of Natural Resources Defense Council (NRDC) Website from English Into Indonesian.” This text was chosen because it is informative and very relevant to the problems in the world that it feels can provide benefits for the readers. This text describes how dangerous climate change is and how the NRDC organization seeks to protect the world, people, plants, animals, and the natural systems on which all life depends. The purpose of implementing this study is to translate texts and apply the translation knowledge gained during the lecture period. This translation process has been carried out from September until December 2022. There were four stages in translating these texts: analysis stage, transfer stage, restructuring stage, evaluation, and revision stage. The analysis stage at this stage reads the entire transcript, the transfer stage is carried out on the brain to analyze and translate the SL to TL, and the restructuring at this stage, the text that has been translated at the transfer stage attempts to restructure. Evaluation and revision, at this stage the evaluation and revision of the translation results are carried out by reading carefully if after rereading there are still words or sentences that are mistranslated, revisions are made to achieve the natural result. During the translation process of the text on climate change from the NRDC (Natural Resources Defense Council) website for example, The obstacles were within selecting the precise word from the source language into the target language, a less-known of understanding of the specific terminology used when translating climate change texts, and limited knowledge of source language idioms which hindered the translation process. The solutions to overcome the obstacles are: consulting with the supervisors, understanding the words or sentences the approach taken during the translation process, look for idiom words in online or offline dictionaries.